2013
DOI: 10.15381/anales.v65i4.1374
|View full text |Cite
|
Sign up to set email alerts
|

Colesterol y triglicéridos como marcadores bioquímicos del estado de la enfermedad del paciente con leucemia linfocítica aguda

Abstract: ResumenObjetivo: Determinar la relación de los niveles séricos de colesterol y triglicéridos con el estado de respuesta al tratamiento quimioterápico de inducción de pacientes con leucemia linfocítica aguda. Material y Métodos: La muestra la conforman 25 pacientes de 2 a 18 años de edad, admitidos al Instituto de Enfermedades Neoplásicas con un diagnóstico reciente de leucemia linfocítica aguda; determinándose en ellos sus concentraciones séricas de colesterol total, colesterol-HDL, colesterol-LDL y triglicéri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Within the increase in glycerolipids, TG was the most relevant. Altered glycerophospholipid metabolism has previously been associated with disease progression in pediatric ALL patients (Yunnuo et al, 2014) and an increase in TG in conjunction with a decrease in CL has been reported in both AML and ALL (Nahid et al, 2013), which has been related to a poor response to treatment (Guzmán and Sandoval, 2004). Particularly, Pabst et al ( 2017) From the point of view of the evolution of the disease, it has been described in other works, that patients with myelodysplastic syndromes who progressed to AL had higher TG levels than those who did not evolve (Qiao et al, 2022) and that in patients with ALL, after a 5-year disease-free period, they developed dyslipidemia with increased plasma TG, increased LDL CL, and decreased HDL CL, which was associated with an increased risk of atherosclerotic disease (Morel et al, 2017).…”
Section: Figurementioning
confidence: 98%
“…Within the increase in glycerolipids, TG was the most relevant. Altered glycerophospholipid metabolism has previously been associated with disease progression in pediatric ALL patients (Yunnuo et al, 2014) and an increase in TG in conjunction with a decrease in CL has been reported in both AML and ALL (Nahid et al, 2013), which has been related to a poor response to treatment (Guzmán and Sandoval, 2004). Particularly, Pabst et al ( 2017) From the point of view of the evolution of the disease, it has been described in other works, that patients with myelodysplastic syndromes who progressed to AL had higher TG levels than those who did not evolve (Qiao et al, 2022) and that in patients with ALL, after a 5-year disease-free period, they developed dyslipidemia with increased plasma TG, increased LDL CL, and decreased HDL CL, which was associated with an increased risk of atherosclerotic disease (Morel et al, 2017).…”
Section: Figurementioning
confidence: 98%